2010
DOI: 10.1093/ejechocard/jeq007
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular myocardial involvement in either physiological or pathological left ventricular hypertrophy: an ultrasound speckle-tracking two-dimensional strain analysis

Abstract: Right ventricular myocardial systolic deformation is positively influenced by preload increase in athletes and negatively associated with increased septal thickness in HCM. Therefore, 2DSE may represent a useful tool in the differential diagnosis between athlete's heart and HCM, underlining the different involvement of RV myocardial function in either physiological or pathological LV hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…The clear prognostic importance of RV function in various diseases has encouraged investigations about new echocardiographic methods for accurate diagnosis of RV failure (2628). In a recently published article, D’andrea et al (29) showed that 2-D-STE-derived RV myocardial systolic deformation is influenced in HCM patients. There was a negative association between inter-ventricular septal thickness and RV global longitudinal strain in HCM patients.…”
Section: Discussionmentioning
confidence: 99%
“…The clear prognostic importance of RV function in various diseases has encouraged investigations about new echocardiographic methods for accurate diagnosis of RV failure (2628). In a recently published article, D’andrea et al (29) showed that 2-D-STE-derived RV myocardial systolic deformation is influenced in HCM patients. There was a negative association between inter-ventricular septal thickness and RV global longitudinal strain in HCM patients.…”
Section: Discussionmentioning
confidence: 99%
“…A few recent studies have utilized RV myocardial speckle tracking to differentiate between physiology and pathology 44–46 and to identify interventional changes 47 . Recent work reported a 36% difference in peak RV ɛ between athletic subjects and those with hypertrophic cardiomyopathy 45 and on the basis of the current data this likely represents a “real” or meaningful difference Conversely, others have demonstrated a difference of 6% in peak RV ɛ between elite athletes and controls 44 and only an 8% reduction in RV ɛ following percutaneous closure of an atrial septal defect 47 . The findings from both of these studies should be interpreted very cautiously on the basis of the current findings for intraobserver variability in this parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Speckle tracking echocardiography of the right ventricle has been already applied to the assessment of the athlete's heart . Recently, D'Andrea et al .…”
Section: Discussionmentioning
confidence: 99%